INNOVATIVE COMPONENT OF TRANSFORMATION OF THE SYSTEM OF PHYSICAL EDUCATION OF STUDENTS IN THE ASPECT OF HEALTHCARE - Tsovh, Larysa; Kuspish, Aleksandr; Zubritsky, Yaroslav; Rozhko, Elena (Mountain School of Ukrainian Carpaty, 2020)
The issues of innovative opportunities for the transformation of students' physical education in the aspect of health saving, as one of the leading directions in the development of the physical education system in higher education institutions the article examines. The new modernization strategy as a priority of reform envisages, first of all, significant changes in the pedagogical theory and practice of physical education. Among the main tasks of the university - solving the problem of supporting and strengthening the health of student youth, creating an atmosphere of health in their education system The purpose of the of the work is to identification and justification of innovative directions of transformation of the physical education system of students of university, aimed at their health saving. Research methods: theoretical analysis, systematization, comparison of different views on the problem under study, generalization of scientific and methodological and specialized literature data. That the need for innovative innovations determines the need for a radical change in the entire process of physical education of students, due to the reorganization of the educational system of Ukraine in accordance with European standards it is established. The main aspects of the implementation of modernization processes in the system of physical education of students for their health care are presented. The value of innovation lies in the use of new techniques and methods of physical education aimed at shaping students' health care needs and skills have been identified. The following are distinguished: interactive technologies of physical education, optimization, a personality-oriented approach, the priority use of individualization and differentiation in classes, the individual choice of types of physical activity in all possible forms of physical education with the active participation of students and the organic synthesis of their elements, according to the results of a scientific study. The practical implementation of a certain contribution to solving the problems of health saving of students, was determined.